A greater understanding of social networks privacy requirements: The user perspective. (April 2017) - Islam, Mohammad Badiul; Watson, Jason; Iannella, Renato; Geva, Shlomo
Abstract: Social Networks (SN) require an accurate understanding of the complex privacy requirements of users to demonstrate respect for user privacy requirements whilst also encouraging sharing. This research extends current understanding of SN user privacy requirements using the PREview approach, drawing on a thematic analysis of related scholarly articles and validating and extending themes by survey. The findings instantiate five primary privacy requirements including: Information Control, Information Collection and Storage, Information Access, Secondary Use, and Social Network Practice, and a further twenty five secondary requirements. This research has the potential to assist with the development of enhanced SN privacy controls.